POTENSI PEMBANGKIT LISTRIK TENAGA MIKROHIDRO (PLTMH) PADA SALURAN IRIGASI DI SUNGAI AESESA KECAMATAN AESESA KABUPATEN NAGEKEO - Wellem Fridz Galla (Jurnal Media Elektro, 2012)
One of energy new to be a real potential is water energy. River Aesesa which located in Aesesa Distrct, Nagekeo can be exploited for Power Station of Microhidro Energy. Nowdays, public only exploit river Aesesa as clean amount of water required and irrigation. This research aim to know level of electricity which can be awakened by Power Station, that is by exploiting one of irrigation channel which there have. Data collecting is done by through measurement of head and water strength. Based on measurement data is gotten by 5.73 m head and water maximum strength 1.399 m3/s yields theoretical energy power 78.56 kW and generator power 48.43 kW. In design applies pipe 24 dim will exploit water strength 0.598 m3/s and pipe 26 dim is 0.95 m3/s which yielding is theoretical energy power 3358 and 5335 kW and generator power 20.7 and 3288 kW.